PATHOMORPHOLOGICAL ASSESSMENT OF THE MORPHOGENESIS OF CHRONIC PLACENTAL INSUFFICIENCY IN TORCH INFECTIONS (BASED ON KARAKALPAKSTAN MATERIALS) - Sharap Iskanderovich Mamutov; Azizbek Amangalievich Atazhanov; Ziyuar Khojabay qizi Alauatdinova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Aim: To evaluate the pathomorphological changes and the morphogenesis of chronic placental insufficiency (CPI) triggered by TORCH infections among pregnant women residing in the Republic of Karakalpakstan. Material and Methods: A macroscopic, histological, and morphometric analysis was conducted on 100 placentas from pregnancies complicated by TORCH infections and CPI, alongside 30 control placentas from uncomplicated physiological pregnancies. Tissue sections were stained using Hematoxylin and Eosin (H&E), Van Gieson, and PAS reaction. Results: The study revealed that TORCH infections lead to profound microcirculatory disorders and inflammatory alterations, notably productive villitis and intervillositis. The structural morphogenesis of CPI in this cohort is characterized by the rapid exhaustion of compensatory-adaptive angiogenesis, giving way to progressive pathological changes including avascular terminal villi, massive fibrinoid necrosis, and severe stroma sclerosis. Conclusion: The synergistic impact of viral/bacterial insults and the underlying environmental stressors in Karakalpakstan accelerates the morphogenetic transition from placental adaptation to decompensation. Early screening and targeted microvascular therapies are highly recommended to mitigate fetal growth restriction.